From Community Gardens to Hybrid Hydroponics: The evolution of northern greenhouses and Arctic gardening - Sipola, Saara Marjatta (UiT Norges arktiske universitet, 2019)
The past and current connections between indigenous peoples and global food production is complicated and multi-dimensional. Agro-ecology and sustainability, as strategies to alleviate global food production problems and, in this case, food insecurity, are consistent with indigenous communities’ traditional food harvesting practices. Historically, their sustainable food systems and culinary traditions have embodied the very essence of sustainability, millennia before it became “invented” by the mainstream societies (Oskal et al. 2018; Egede, 1998). In this context, Northern greenhouse development and Arctic gardening emerge as viable solutions toward addressing food insecurity, retaining food sovereignty, and creating opportunities for development. The aim of my thesis is to illustrate the importance of local food systems for indigenous peoples, and the efforts undertaken so far, to address food security and regional development in the North. My work looks at the intersection of food security and development through an examination of the evolution of Arctic gardening in the Arctic, with a focus on Nunavik, one of the four regions of Inuit Nunangat in Canada. More specifically, I look to the community of Kuujjuaq, located in Nunavik. Using secondary, published data, and primary source data, including interviews and participant observation, I address the following research questions in this thesis: What impacts can be identified from the development of community gardens and greenhouses in the North and how can gardening contribute to increased food security?